A Review on Triple Antibiotic Paste as a Suitable Material Used in Regenerative Endodontics - Mohammadi, Zahed; Jafarzadeh, Hamid; Shalavi, Sousan; Yaripour, Shapour; Sharifi, Farid; Kinoshita, Jun-Ichiro (Iranian Endodontic Journal, 2019)
As the root canal system shows different and complicated anatomies, mechanical instrumentation alone has not the ability to provide a bacteria-free environment in root canals. On the other aspect, necrotic tissue remaining can decrease the effects of root canal irrigants and medicaments and also interfere with the adaptation of root canal fillings to dentin. As a result, certain disinfection and irrigation procedures are required to remove the remaining tissues from the root canal area thoroughly and also be able to eliminate the microorganisms. Triple antibiotic paste (TAP) containing metronidazole, ciprofloxacin and minocycline has been proposed as a root canal medicament due to its antimicrobial effects in endodontic regenerative procedures. The purposes of this review were to determine the properties of TAP drugs and to evaluate the efficiency of TAP on the root canal disinfection, in primary and permanent teeth, along with its affection in regeneration/revascularization procedures. The biocompatibility and disadvantages of this medicament were also discussed. Keywords: Endodontics; Intra-canal Medicament; Regeneration; Triple Antibiotic Paste